2016
DOI: 10.1080/02615479.2016.1188915
|View full text |Cite
|
Sign up to set email alerts
|

Debunking macro myths: findings from recent graduates about jobs, salaries, and skills

Abstract: Research suggests that interest in macro social work practice is declining, a trend that has been well documented in the United States. Studies find that social work educators and practitioners may foster beliefs among MSW students that discredit macro practice and associated skills while asserting macro graduates are likely to face poorer employment prospects and lower salaries than micro counterparts as they start their careers. This study builds on and extends this literature by examining 27 skills in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Choi et al (2015) found that graduates with specializations in micro/direct practice were more likely to find a job matching this focus (91%), compared to graduates with a macro specialization matching related employment (64%). However, Zerden et al (2016) report that while MSW students with a macro concentration were less likely to find a macro-oriented job directly after graduation, they continued to use macro-related skills 58% of the time, with no significant difference noted either in the time it took to find employment or the salary of graduates with micro and macro concentrations. Pritzker and Applewhite (2015) found supporting evidence that macro-trained social workers compete well for jobs and report higher salaries than the social work averages.…”
Section: Implications For Social Work Field Researchmentioning
confidence: 96%
“…Choi et al (2015) found that graduates with specializations in micro/direct practice were more likely to find a job matching this focus (91%), compared to graduates with a macro specialization matching related employment (64%). However, Zerden et al (2016) report that while MSW students with a macro concentration were less likely to find a macro-oriented job directly after graduation, they continued to use macro-related skills 58% of the time, with no significant difference noted either in the time it took to find employment or the salary of graduates with micro and macro concentrations. Pritzker and Applewhite (2015) found supporting evidence that macro-trained social workers compete well for jobs and report higher salaries than the social work averages.…”
Section: Implications For Social Work Field Researchmentioning
confidence: 96%
“…Research has also found that macro practice students were often told by social work educators that it is difficult to obtain a job and pass the licensing exam with a concentration in macro practice -which perhaps speaks to the content of licensing exams (Plitt Donaldson et al, 2016). Social work students often perceived their foundational social work courses to be void of relevant examples of macro practice and social work administration (Ezell et al, 2004;Zerden et al, 2016). Likewise, faculty members who teach macro practice often feel unsupported by their departments and institutions while teaching macro content (Rothman, 2013).…”
Section: Students' Perceptions Of Macro Social Work Educationmentioning
confidence: 99%
“…Agencies need to address the issue of succession planning, and schools of social work need to prepare and equip graduates to take on leadership roles. De-emphasizing macro-level administration and leadership training in schools of social work in favor of direct service and clinical training is well-documented (de Saxe Zerden, Sheely, & Despard, 2016;Ezell, Chernesky & Healy, 2004;Rank & Hutchison, 2000). As a result, an increasing number of human service agencies are being led by executives with degrees from disciplines other than social work (Packard, 2004;Patti, 2003).…”
mentioning
confidence: 99%